Lean Construction Approach to Material Waste in the Construction Project of Elementary School Building 6 Kajarharjo Banyuwangi - Harliwanti Prisilia; Dimas Aji Purnomo (Universitas Islam Raden Rahmat, Malang, 2025)
Lean Construction is a method that focuses on minimizing waste and increasing added value in the construction process. This research aims to identify and analyze material waste that occurs in the SDN 6 Kajarharjo building construction project, Banyuwangi, by applying the Lean Construction approach. Material waste is one of the significant factors in reducing efficiency and increasing project costs. The research method used is field observation, interviews with related parties, and data analysis based on the principles of Lean Construction, especially in identifying material waste based on the main work done in the building construction project. The results showed that the waste materials that occurred in this project were 19.44 m2 of red brick material, 0.34 kg of plain iron 8, 74 kg of plain iron 10, 14 kg of plain iron 12, 79.60 kg of screw iron 13, 34.90 kg of formwork, 6 m3 of split stone and 3 m3 of ready mix concrete. With the implementation of the Lean Construction approach, it is expected that the SDN 6 Kajarharjo building project can achieve better material efficiency, reduce costs, and improve overall construction quality.